Reimplantation or implantation in dental avulsion, what has changed in these last years? The narrative review (Research, Society and Development, 2022)
Tooth avulsion is one of the urgent situations that can influence masticatory physiology, aesthetic issues and affect the patient's quality of life. For the treatment of this misfortune, a replantation or dental implant may be indicated. Objective: Faced with the possibility that new practices and/or clinical evidences have emerged in the last ten years in the use of reimplantation or implant techniques in traumatic dental avulsion, the present narrative review proposed a brief discussion, in the perspective of contributing to a more efficient therapy. and an improvement in the patient's quality of life. Methodology: The search strategies were structured from MeSH terms/ and DeCS/MeSH terms, in the /PubMed database, and manual search, for the terms: Tooth avulsion, Traumatic dental injury; Tooth replantation, Dental implantation. Articles were included, accessible in full, that addressed the technique of reimplantation or dental implant after traumatic avulsion, in humans, without language restriction and published until 2022. Letters to the editor and opinion texts were excluded. Conclusion: The practice of dental reimplantation shows few changes over the years, according to this review. It consists of a rescue treatment, even considering a careful clinical evaluation and based on already established protocols, since there is still no consensus on reimplantation in traumatic avulsion. On the other hand, procedures related to implants, often associated with the use of graft materials and membranes, have been presented as an excellent option in the correction of tooth loss.